Successful Use of Dupilumab in Bullous Pemphigoid: A Series of 3 Cases in Mexico - Belmont Nava, Pablo; Carol Estefania Márquez-Maldonado; Lucia Achell Nava; Guadalupe Maldonado Colin; Dolores Maribel Arellano Vivero (International Journal of Medical Science and Clinical Research Studies, 2025)
This review explores three recent case reports detailing the successful treatment of bullous pemphigoid (BP) with Dupilumab, a monoclonal antibody targeting interleukin-4 receptor alpha subunit (IL-4Rα). Each case highlights unique clinical presentations, treatment approaches, and outcomes, underscoring Dupilumab's potential as a therapeutic option in BP management.